Symptom patterns in patients newly sick listed for common mental disorders and associations with work-related and socioeconomic factors: a cross-sectional study in Swedish primary care - Cecilia Björkelund; Dominique Hange; Eva-Lisa Petersson; Irene Svenningsson; Nashmil Ariai; Lilian Wiegner (BMJ Open)
Objective The aim was to determine symptom patterns of depression, anxiety and stress-related mental disorders in newly sick listed due to common mental disorders in Swedish primary care patients and to examine associations with sick leave diagnosis, also in relation to socioeconomic, work-related and demographic factors.Design Cross-sectional study.Setting Primary care in western Sweden.Participants From a randomised controlled trial, patients aged 18–67, seeking primary care and on sick leave due to depression, anxiety and/or mental stress, in total 341 individuals, during 2018–2020.Primary outcome measures Patterns of depressive, anxiety and stress symptoms measured via self-assessment questionnaires (Montgomery Asberg Depression Rating Scale-Self (MADRS-S), General Anxiety Disorder Scale-7 (GAD-7), Karolinska Exhaustion Disorder Scale (KEDS)), sick leave diagnosis, perception of Work Ability Index and job strain via the job strain model.Results A combination of high levels of depressive and stress-related symptoms was more frequent than single symptom clusters among persons with common mental disorders (CMD) on sick leave: 7% of the patients had scores above cut-off for one of the instruments MADRS-S, GAD-7 and KEDS, 12% above cut-off for two and 80% had above cut-off for all three instruments. There was no significant association between low socioeconomic status, high-job strain or working in healthcare/education and having scores above cut-off level for two or more of the instruments. Only perception of own poor work ability showed association with having scores above cut-off level for all three of the assessment instruments of CMD (OR 9.45, 95% CI 2.41 to 37.04).Conclusion The diagnosis on the sick certificate is not always congruent with the dominating symptom score level. In patients sick-leaved for CMDs, possible negative factors such as low socioeconomic status, low social support, high-work strain or working in healthcare/education sector did not show significant associations with self-assessment instruments of anxiety, depression and stress. Only patient’s perception of own poor work ability was associated with high scores on all three domains.Trial registration number NCT03250026.